Best Practices of Instructional Leadership among Principals of Primary and Secondary Schools in Male’, Maldives - Shujau-Abdul-Raheem, Mohamed (International Journal of Scientific Research and Management (IJSRM), 2023)
The purpose of this study was to examine the best practices of instructional leadership among principals of primary and secondary schools in Male’, Maldives, based on teachers’ perceptions. The Principal Instructional Management Rating Scale (PIMRS), developed by Hallinger and Murphy (1985) and modified by Hallinger and Wang (2015), served as the instrument for data collection through a questionnaire. A total of 392 teachers from schools in Male’, Maldives, were surveyed and data were analyzed using SPSS 26.0.  The result of the study shows that all three dimensions of instructional leadership—"defining the school mission" (mean 4.05), "managing the instructional program" (mean 3.94), and "developing a positive school learning climate" (mean 3.72)—have reached a high level in practice. The study shows that the three best practices of principals in instructional leadership are to effectively communicate the school's mission to members of the school community (dimension 'Defining the School's Mission', mean 4.12), to clarify who is responsible for coordinating the curriculum across grade levels (dimension 'Managing the Instructional Program', mean 4.29), and to encourage teachers to use class time to teach and practice new skills and concepts (dimension 'Developing a Positive School Climate', mean 4.10). It is hoped that this study will provide useful insights that will be effective in improving the instructional leadership skills of principals to improve the academic performance of students and create a world-class human capital that is comparably excellent.